Uma análise das imagens estereotipadas da mulher brasileira na mídia - Souza, Lisani Albertini de (2010)
This dissertation analyzes the process of formation of the stereotype of the Brazilian woman in a variety of media, from the 16th century to the present. Although this research corpus appears to be too broad, a few specific contents were chosen to guide the main hypothesis that Brazilian female stereotypes are memes that emerge from complex cultural relationships established since the period of colonization of Brazil, which have survived thanks to adaptive processes that include the action of the media (print, electronic and digital), but are not restricted to them. As the theoretical foundation, we start from the notion of body-media (Katz & Greiner 2005), shifting the theme from the sphere of Sociology and Feminist Studies to the field of communication and evolutionary studies. To this end, we negate some simplistic causal relationships in favor of systemic relationships generated in different mediatic environments. To deepen the analysis of some images, we also use the work of Serge Gruzinski (2001), who discusses Latin American culture based on the concept of miscegenation, recognizing civilizatory differences in constant interaction, as well as the studies of Homi Bhabha (2003) and Boaventura de Souza Santos (2008) about cultural mimesis and the ambivalence of image translation processes between cultures. As a result, we present a collection of images and their respective analyses